The The Effect of Training Effectiveness on Employee Performance with Motivation as a Mediator at the State Assets and Auction Services Office (KPKNL) in Medan - Parsan, Parsan; Meutia, Meutia; Soesanta, Prabawa Eka (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of training effectiveness on employee performance with motivation as a mediating variable. The research method employs a quantitative approach, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Data were obtained by distributing questionnaires to all 44 employees of KPKNL Medan and analyzed using SmartPLS with bootstrapping tests. The results showed that training effectiveness, as measured by the Kirkpatrick Model, had a positive and significant effect on employee performance (b = 0.356; p < 0.001) and on motivation based on Self-Determination Theory (b = 0.843; p < 0.000). Motivation was also shown to have a significant effect on performance (b =0.613; p<0.000) and mediated the relationship between training effectiveness and performance with a greater indirect effect (b =0.517) than the direct effect. These findings confirm that motivation is an important mechanism that explains how effective training can have a real impact on performance improvement. This research provides theoretical contributions by integrating the Kirkpatrick model and Self-Determination Theory, as well as practical implications for management at KPKNL Medan in designing training programs that not only improve technical competence but also increase employee work motivation.